STUDY OF THE CHANGE Polyamide (PA) NET YARN IMMERSION IN FRESH WATER AND SEA WATER - Tri Rahmadhani; Irwandy Syofian; Polaris Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in April 5 to May 15, 2017 in Laboratory of Fishing Gear Material of Aquatic Resources Faculty of Fisheries and Marine University of Riau, Pekanbaru. The purpose of this research is to know the increase of PA net yarn length after soaking in fresh water and sea water. The method used in this research is the experimental method, the result data for changes of the length net yarn is processed using the formula according to SNI 08-0889-1989 and then analyzed descriptively. From the result of this research, there are changes of polyamide (PA) yarn length after soaked in fresh water and sea water with average length will change after soaking in freshwater and sea water of 1002.51 mm and 1002.89 mm while average change of length after several condition in freshwater and seawater of 1002.51 mm and 1002.79 mm. The authors suggest to do for further research on the changes of the net yarn length after soaking in freshwater and sea water with the addition of soaking time and conducted research on the tensile strength of PA yarn after immersion.Keywords: Changes Of Net Yarn, Fresh Water, Sea Waters